STA-9090 in combination with a statin exerts enhanced protective effects in rats fed a high-fat diet and exposed to diethylnitrosamine and thioacetamide - Abdelhamid, Amir Mohamed; Saber, Sameh; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; Ellethy, Abousree T.; Amer, Maha M.; Abdel-Hamed, Mohamed R.; Mohamed, Enas A.; Ahmed, Syed Suhail; Elsisi, Hossam A.; Khodeir, Mostafa M.; Alkhamiss, Abdullah S.; et al. (Frontiers in Pharmacology, 2024)
Liver fibrosis is a significant global health burden that lacks effective therapies. It can progress to cirrhosis and hepatocellular carcinoma (HCC). Aberrant hedgehog pathway activation is a key driver of fibrogenesis and cancer, making hedgehog inhibitors potential antifibrotic and anticancer agents. We evaluated simvastatin and STA-9090, alone and combined, in rats fed a high-fat diet (HFD) and exposed to diethylnitrosamine and thioacetamide (DENA/TAA).Simvastatin inhibits HMG-CoA reductase, depleting cellular cholesterol required for Sonic hedgehog (Shh) modification and signaling. STA-9090 directly inhibits HSP90 chaperone interactions essential for Shh function. We hypothesized combining these drugs may provide liver protective effects through complementary targeting of the hedgehog pathway. Endpoints assessed included liver function tests, oxidative stress markers, histopathology, extracellular matrix proteins, inflammatory cytokines, and hedgehog signaling components. HFD and DENA/TAA caused aberrant hedgehog activation, contributing to fibrotic alterations with elevated liver enzymes, oxidative stress, dyslipidemia, inflammation, and collagen deposition.Monotherapies with simvastatin or STA-9090 improved these parameters, while the combination treatment provided further enhancements, including improved survival, nearnormal liver histology, and compelling hedgehog pathway suppression. Our findings demonstrate the enhanced protective potential of combined HMG CoA reductase and HSP90 inhibition in rats fed a HFD and exposed to DENA and TAA. This preclinical study could help translate hedgehog-targeted therapies to clinical evaluation for treating this major unmet need.